Implementation of Government Regulation No. 28 of 2024 on Legal Abortion to Ensure Legal Certainty - Setiawati, Faika Pra; Juliana, Nur Lita; Siroj, Mohamad; Nurhaqi, Ari; Harliyanto, Rois (PT FORMOSA CENDEKIA GLOBAL, 2025)
Abortion is a complex and sensitive issue that involves legal, moral, social and religious aspects. In Indonesia, abortion is generally criminalized, except under certain conditions under Government Health Law No. 17 of 2023 and Government Regulation No. 28 of 2024. These regulations allow for legal abortion in cases of medical emergency or as a result of sexual violence. This study analyzes the implementation of these Government Regulations in hospitals and the response of medical personnel to them. Using normative and empirical juridical qualitative methods, data was obtained through literature study and interviews with gynecologists in Cirebon. The results show that there are still many obstacles, such as limited facilities, complicated procedures, and lack of an integrated system. Socialization, training, and clear Standard Operating Procedures (SOPs) are needed for the protection of women.